Development of the Mandarin pediatric speech intelligibility (MPSI) test. - Zheng Y; Soli SD; Wang K; Meng J; Meng Z; Xu K; Tao Y (International Journal of Audiology, 2009)
The objective of this research was to create a Mandarin closed-set sentence recognition test based on the English pediatric speech intelligibility (PSI) test (Jerger & Jerger, 1984) for evaluation of speech perception in children as young as three years of age. Developmentally normal children (N=93), 3--6 years of age, were administered the Mandarin PSI (MPSI) via a computer-controlled protocol. Perfect performance was observed for all children in quiet and at +10 and +5 dB signal-to-noise ratios (SNRs). Significant age and developmental trends were seen for the more difficult SNRs, 0 dB, -5 dB, and -10 dB, with 75% of 5--6 year olds reaching the most difficult SNR. Children who reached each of the more difficult SNRs, regardless of age, exhibited the same pattern of performance on all easier conditions, indicating that the final SNR achieved, rather than percent correct scores, may be a better descriptor of performance. The MPSI comprises part of a hierarchical assessment battery for pediatric speech perception for evaluation of intervention alternatives for Mandarin-speaking children with hearing impairment.